An Efficient 2D Rough Surface Scattering Analysis Using Strong Harmonics Extraction and the Kirchhoff Approach - Torabi, A.; Shishegar, A. A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An efficient method for scattering analysis from slightly rough surfaces is introduced. This method can be used in ray tracing algorithm where the computational efficiency is important due to the complexity and size of problems. In this method, the Kirchhoff approach is used for a periodic extension of the finite surface, which is approximated by strong harmonics of its Fourier series. Typical asphalt surfaces are analyzed by this method in millimeter-wave band and validated with the method of moments. The dominant scattering angles and ray widths of the scattered field can be easily used in ray tracing algorithm. The computation time and accuracy of results show that this method can be used for rough surface scattering analysis in ray tracing algorithm efficiently.